Optimalisasi Branding dan Legalitas Usaha dalam Upaya Peningkatan Daya Saing UMKM di Desa Kebumen Baturaden - Shafrani, Yoiz Shofwa; Wahyuningtyas, Ida Puspitarini; Destiana, Diah Sari; Ayuni, Titi Salma (Universitas Pahlawan Tuanku Tambusai, 2026)
The majority of businesses in Kebumen Village, Baturaden, are still small, informal traders, with the main problems being low business legitimacy (NIB and Halal Certification) and a lack of professional branding skills. This hinders the competitiveness of local products on the broader market. The objective of this community service programme is to transform 20 small business groups into formal MSMEs by strengthening the legality and branding of their leading products. The method used is Asset-Based Community Development (ABCD), which focuses on local potential through workshops and intensive technical assistance. As a result, there has been a significant increase in the awareness and commitment of business owners to obtain NIB and Halal Certification. Tactically, packaging prototypes and rebranding stickers have been produced, which enhance the visual value and credibility of the products. This programme has successfully laid the foundations for business professionalism and legality. Legality and a strong brand identity are crucial foundations for MSMEs to increase market access, capital, and achieve sustainable business growth.